PERFORMA AYAM BROILER PADA JARAK INLET YANG BERBEDA DI KANDANG TIPE CLOSED HOUSED - Daryatmo Daryatmo (Universitas Islam Balitar, 2021)
The objective of this study was to determine the effect of zonation in the closed house enclosure on its microclimate conditions and the physical appearance of broilers. This study used 22,000 day old cobb strains broilers divided into four zonation area, i.e., zone 1 = an area 0-30 m from the inlet, zone 2 = 30-60 m from the inlet, zone 3 = 60-90 m from the inlet, and zone 4 = 90-120 m from the inlet. Air temperature and humidity of each zone were recorded daily from day 7 to day 21 st of the rearing period.. On day 28st, a total of 360 chicks were selected randomly from 90 chick each zone for bodyweight and Uniformity. This study shows that the environmental conditions of the enclosure were characterized by a tendency for the temperature to increase in the area away from the inlet, on the contrary, the humidity level decreased. However, the differences in the value of these environmental parameters can still be tolerated by chickens, which are body weight, uniformity and mortality by a fairly normal score. The different zonation in the closed house for broilers was fairly enough to provide a good environmental condition for broilers as observed from broiler performance.